2017
DOI: 10.1080/10408398.2015.1110111
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of myofibrillar proteins in water or low ionic strength media: Classical techniques, basic principles, and novel functionalities

Abstract: The qualitative characteristics of meat products are closely related to the functionality of muscle proteins. Myofibrillar proteins (MPs), comprising approximately 50% of total muscle proteins, are generally considered to be insoluble in solutions of low ionic strength (< 0.2 M), requiring high concentrations of salt (> 0.3 M) for solubilization. These soluble proteins are the ones which determine many functional properties of meat products, including emulsification and thermal gelation. In order to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 132 publications
0
47
0
Order By: Relevance
“…Protein Extractability. Solubility is an indicator of protein extractability; indeed, a solubilized protein could be easily extracted into a solution from muscle fibers or myofibrils [9]. e amount of myofibrillar proteins extracted using denaturing and nondenaturing solutions from beef, lamb, chicken, sole, European hake, and sea bass is reported in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein Extractability. Solubility is an indicator of protein extractability; indeed, a solubilized protein could be easily extracted into a solution from muscle fibers or myofibrils [9]. e amount of myofibrillar proteins extracted using denaturing and nondenaturing solutions from beef, lamb, chicken, sole, European hake, and sea bass is reported in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has to be considered that the use of these reagents is regarded as toxic and highly polluting and require proper disposer procedures. Chen et al [9] reported the use of water or low ionic strength media for the extraction and solubilization of myo brillar proteins from skeletal muscle. To the best of our knowledge, no research is available on the comparison of the extraction capacity of denaturing and nondenaturing solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal gelation of MPs involves partial denaturation of protein followed by irreversible aggregation, which forms a multidimensional network that holds water and thus produces a gel (Sun & Holley, ). It is generally accepted that a high concentration (2% to 3% or >0.3 m ) of sodium chloride (NaCl) is required to solubilise the MPs to form a good gel, improving textural properties and water‐holding capacity (WHC) (Lee et al ., ; Cando et al ., ; Chen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, many meat by-products are rich in proteins and if processed correctly can be used for the production of extracts with desirable functional properties (Chernukha et al, 2015;Lynch et al, 2018). It is well known that myofibrillar proteins are mainly responsible for the gelling properties of meat products (Chen et al, 2015). The production of protein rich extracts from meat by-products represents a good valorisation opportunity for the meat industry, and at the same time can improve consumer acceptance.…”
Section: Introductionmentioning
confidence: 99%